An analysis of the safety profile of proteasome inhibitors for treating various cancers. (August 2014) - Wang, Hui; Guan, Fangxia; Chen, Di; Dou, Qing Ping; Yang, Huanjie
<x xml:space="preserve">Abstract</x> Introduction: Emerging evidence demonstrates that the ubiquitin-proteasome pathway is a promising target for cancer therapy. Bortezomib (Velcade) exhibits great efficacy against multiple myeloma (MM) since the first clinical application. However, there are still several limitations associated with the use of bortezomib, including severe toxicities. To overcome bortezomib's shortcomings and to improve its safety profile, several second-generation proteasome inhibitors, for example, carfilzomib, ixazomib, oprozomib and marizomib, have been developed and currently tested in various clinical trials. Areas covered: A literature search was carried out using PubMed and Google Scholar. The activity and safety profiling of proteasome inhibitors in treatment of various cancers were reviewed. Expert opinion: Bortezomib, as a single or in combination therapy, demonstrates efficacy against MM or other hematological malignancies in clinical settings. However, it encounters two major problems, the acquired resistance and the severe side effects. Future direction in bortezomib-based therapy should focus on how to increase or retain its efficacy but improve its safety profile through, for example, rational combination therapies. Second-generation proteasome inhibitors have shown benefits in both overcoming bortezomib resistance and reducing related side effects, although these encouraging results should be further confirmed in a larger clinic population.